Three-dimensional thermal stress analysis using the indirect BEM in conjunction with the radial integration method. (October 2017) - Qu, Wenzhen; Zhang, Yaoming; Gu, Yan; Wang, Fajie
Highlights: A transformation system is constructed to eliminate singular integrals. The radial integration method converts domain integrals into boundary integrals. The boundary displacement gradient in any direction can be evaluated. The developed method is accurate and has a high convergence behavior. Abstract: Thermal stress analysis is one of key aspects in mechanical design. Based on the indirect boundary integral equation (BIE) and the radial integration method (RIM), this paper develops a boundary-only element method for the boundary stress analysis of three-dimensional (3D) static thermoelastic problems. A transformation system constructed with the normal and two special tangential vectors is used to regularize the singularity in the indirect BIE. The RIM is then employed to transform the domain integrals arising in both displacement and its derivative integral equations into the equivalent boundary integrals, which results in a pure boundary discretized algorithm. Several numerical experiments are provided to verify the accuracy and convergence of the present approach.